Holocene surface hydroclimate changes in the Indo-Pacific warm pool. (20th July 2018) - Li, Ziye; Chen, Min-Te; Lin, Da-Cheng; Wang, Houjie; Shi, Xuefa; Liu, Shengfa; Yokoyama, Yusuke; Yamamoto, Masanobu; Shen, Chuan-Chou; Mii, Horng-Sheng; Troa, Rainer Arief; Zuraida, Rina; et al.
Abstract: The Indo-Pacific warm pool (IPWP) is an area hosting key tropical climate processes such as the El Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). The tropical climate processes, via various feedback mechanisms, control the surface ocean climate in the Indian Ocean and its surrounding continents on annual to inter-annual timescales. However, little has been known about how the tropical processes are effective forcing climate mechanism over longer timescales. Here we presented a reconstruction of the spatiotemporal pattern of sea surface temperature (SST) with inferred hydroclimate changes since the early Holocene (∼11ka), using proxies of planktonic foraminifer shell Mg/Ca, organic biomarker (TEX86 ), foraminifer oxygen isotopes, and a terrigenous BIT index measured from a 220 cm long Core BS24 (2.724041°N, 97.010943°E, 1015 m water depth) which was taken offshore of northwest Sumatra in the eastern Indian Ocean. With an age model of 13 AMS 14 C dating by the uses of planktonic foraminiferal shells from the core, the TEX86 H temperatures of BS24 show as summer-weighted, and reflect integrated thermal effects from the surface to thermocline water, while the Mg/Ca temperature of BS24 better reflects mean annual SST. Our results, along with a regional synthesis of published SST records from the IPWP, suggest that the IPWP has migrated eastwardly since the mid-Holocene (∼5ka). In phase with this eastward migration, the IPWP SSTs have decreased, but the upwelling in the eastern Indian Ocean appears to have been a persistent feature since the mid-Holocene. Our Empirical Orthogonal Function (EOF) analysis on the compiled IPWP SST records indicates two dominant modes of spatio-temporal variability of surface hydrographes in the IPWP that are attributed to a combined effect of orbital and solar forcing, with expressions analogous to the Indian ocean basin-wide mode (IOBM) and the Indian Ocean dipole model (IOD).